Risco de lesão por pressão em pacientes submetidos à cirurgia de coluna - Souza, Gabriela Goes Botelho de; Federico, Wanessa Alves; de Carvalho, Rachel (Revista SOBECC, 2023)
Objective: To verify the risk of pressure injury in patients undergoing spine surgery and analyze the associated risk factors. Method: This is a descriptive-exploratory, cross-sectional field research, with quantitative analysis carried out in two stages (pre-operative and intraoperative), with 55 patients undergoing spine surgery, in a private hospital in São Paulo, Brazil, through the application of a characterization form of the participant and the surgery and the application of the Risk Assessment Scale for the Development of Injuries due to Surgical Positioning (ELPO). Results: According to ELPO, 33 of the 55 patients (60.0%) had a higher risk score for pressure injury. Patients at highest risk had an average age of 50.2 years, classified as overweight and obese, and had a mean surgery time of 2 hours and 45 minutes. There were significant statistical differences between the higher and lower risk groups, related to: age, weight, body mass index, and surgery time. The patient’s risk of developing a pressure injury increases proportionally with increasing age, weight, body mass index, and surgery duration. As these factors increase, the patient’s risk of developing pressure injury increases. Conclusions: The risk of pressure injury related to spinal surgical procedures was significant, evidencing a reality in which the perioperative nurse is responsible for planning preventive measures to mitigate the occurrences of such injuries and ensure patient safety.